2017
DOI: 10.17159/2310-3833/2017/v47n3a7
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy graduates' reflections on their ability to cope with primary healthcare and rural practice during community service

Abstract: Health reform in post-apartheid South Africa (SA) has been geared to improve health outcomes and rectify historical inequalities 1,2. The majority of the SA population (70%) generally access the public health system while only 18,4%, with medical insurance, access the much better resourced-private healthcare system 3. The district health system facilitates the delivery of services in the public sector through geographically-zoned districts where services are offered at quaternary, tertiary, secondary, district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 15 publications
4
24
0
1
Order By: Relevance
“…In South Africa, most therapists with less than 2 years of experience will be doing community service in rural or underserved areas where working conditions are relatively challenging (Naidoo et al 2017;Singh et al 2015). Hence, newly qualified therapists will be more attracted to CPD activities that offer them opportunities to learn through practical and interprofessional approaches (Naidoo et al 2017), and this was confirmed in this study.…”
Section: Discussionsupporting
confidence: 68%
“…In South Africa, most therapists with less than 2 years of experience will be doing community service in rural or underserved areas where working conditions are relatively challenging (Naidoo et al 2017;Singh et al 2015). Hence, newly qualified therapists will be more attracted to CPD activities that offer them opportunities to learn through practical and interprofessional approaches (Naidoo et al 2017), and this was confirmed in this study.…”
Section: Discussionsupporting
confidence: 68%
“…There are very few plans aimed at recruitment and retention of occupational therapists beyond community service to the public sector. The lack of posts in the public sector is one of the primary reasons for poor retention of community service therapists [30]. Other push factors include restricted resources, poor supervision, cultural incompetence, feelings of unpreparedness for the skill set required [7,9,22,31] negative exposure to rural and urban experiences during training, favouring urban over rural placements, proximity to home, family contact, relationships and dependents [32].…”
Section: Discussionmentioning
confidence: 99%
“…Witchger-Hansen and Blaskowitz 75 demonstrate a successful occupational therapy community-based vocational training program for Tanzanians with physical disabilities, finding improvements in occupational performance ratings specifically in regards to involvement in income-generating activities. Understandably, this requires African occupational therapy educational programs to incorporate CBR skill development, including skills in program development, evaluation and management, particularly through practice placements in local community settings, to ensure therapists are knowledgeable and competent in CBR practice approaches [75][76][77][78] .…”
Section: The Role Of Occupational Therapy In Africa Related To Practicementioning
confidence: 99%